Priority Recommendations for Residential Road Improvement Using the SMART Analysis Method - Sumaryanti, Lilik; Nugraha, Syaiful; Lamalewa, Lusia (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
Roads are infrastructure for organizing transportation, which are places for traffic to flow both for people and goods to reach destinations safely, securely, comfortably, quickly, smoothly, orderly, and efficiently, especially roads in residential areas. Setting priorities for the road improvement program is the responsibility of the Public Housing, Settlement Areas, and Land Affairs Office, which handles technical planning, development, arrangement, supervision, and control of development in residential areas. Recommendations for road proposals for the currently running improvement program, based on an assessment of their physical condition, are carried out by experts. This prioritization certainly takes a long time because experts have to compare the physical conditions of the roads one by one to make a decision. A decision support system is specifically designed for the decision-making process that can be applied in various aspects of the decision-making field. Recommendations for alternative roads in the road improvement program were analyzed using the SMART method to find alternatives with the highest preference value and the advantage that they can be used for all weighting techniques. Accuracy testing shows that the priority recommendation output presented by the application has an accuracy rate of 80%. This value is obtained by comparing the results of recommendations from experts.